Risk management in an educational cooperative - Santos, Breno de Oliveira; Nico Filho, Gelson Heraldo; Celeste, Wanderley Cardoso; Xavier, Thiago Padovani (Brazilian Journal of Production Engineering, 2024)
All organizations are inclined to face risks in their business model. It is relevant to analyze the governance practices in an educational cooperative in the consumer sector, as it may enable the identification of the risks inherent to this business model. The objective of this study was to analyze the governance structure and the risks involved in an educational cooperative located in the city of São Mateus-ES. Data were collected from documents provided by the institution. The governance structure and its alignment with the cooperative principles were evaluated based on the OCB cooperative management manual and by the ISGC from 2019 to 2022. The risks were identified, analyzed, and evaluated according to the PGR of the ISO 31000 and classified using the Risk Matrix tool. The suggestions for risk treatment were based on improvements proposed in similar literature. It was observed that governance follows cooperative principles and the GSGC went from 55.76% in 2019 to 60.90% in 2022 and the risks identified are considered medium or high. After analyzing the results, it was concluded that the risk of default should be a priority for treatment, due to the impact that its occurrence may generate.